Pengaruh Substitusi Pozolan Alam (Tras) terhadap Semen pada Kuat Tarik Campuran CTRB - Waani, Joice; Prabandiyani, Sri; H Setiadji, B (Department of Civil Engineering, Diponegoro University, 2014)
The use of Cement Treated Recycling Base (CTRB) material in Indonesia, is a very well established practice in Indinesia. This mixture containing Reclaimed Asphalt Pavement (RAP) and Reclaimed Aggregate Materials (RAM) and stabilized with portland cement as pavement structural base layer. This technique has been applied in the field in some pavement major rehabilitationand reconstruction projects successfully. However, identical to other cementitious stabilized materials, this CTRB material is prone to cracks during service. For that reason, the use of cement as a stabilized material in CTRB has to be reviewed thoroughly before implementation in the field. The use of recyclable materials in pavement applications is not only environmentally friendly, but also can reduce the cost of materials in a particular project. In addition, a reduction in the use of cement in the CTRB material has a potential to reduce anticipated cracks that influence the physical characteristic of the mixtures. In this research project, the Indirect Tensile Strength (ITS) Test was conducted to review the influence of partial cement replacement with natural pozzolan (trass) to the mechanical properties of the CTRB to withstand tensile stress. A lower ITS value correlates to the shrinkage cracking tendency of the material. The results show that the increase in the percentage of cement replacement correlates well to the increase of the ITS values. Direct correlations exist for 15% and 30% cement replacement of the 4% to 6% CTRB cement content with 40% RAP-60% RAM and 60% RAP – 40% RAM combinations.